Assessment of the Therapeutic Potential of Nimbadi Churna and Kokilakshadi Kwath in Managing Vatarakta (Gout): A Randomized Comparative Clinical Study (AYUSHDHARA, 2024)
The rise in hyperuricemia, often linked to changing dietary habits, has increased the global prevalence of gout, affecting 2.1 million people with a prevalence of 0.2-0.6%. Gout is indicative of underlying comorbidities such as obesity, diabetes, hypertension, and renal diseases. In contemporary medicine, Vatarakta is likened to gout due to shared causes and symptoms, involving the vitiation of Vata and Rakta by distinct etiological factors, and the restricted movement of vitiated Vata by vitiated Rakta leads to Vatarakta. While asymptomatic hyperuricemia may not necessitate intervention, clinically manifest gout requires long-term treatment to lower uric acid levels and acute pain relief. Current medications like allopurinol, uricosuric agents, NSAIDs, colchicine, and glucocorticosteroids carry mild to severe side effects. Recognising the need for an effective, affordable, and well-accepted treatment. The study assessed the efficacy of Nimbadi Churna and Kokilakshadi Kashay in managing Vatarakta through an open, randomized clinical trial with 60 patients. Both treatments were administered for 28 days. Dosages were 3gm B.I.D for Nimbadi Churna and 40ml B.I.D for Kokilakshadi Kashay. Four follow-ups were performed every 7th day, assessing subjective parameters via grade scores and serum uric acid levels. Results indicated both treatments were significantly effective (p0.05). Nimbadi Churna and Kokilakshadi Kashay demonstrated notable efficacy in Vatarakta management, presenting promising alternatives with minimal complications. While further research is necessary for validation, these findings highlight the promise of Ayurvedic approaches in the comprehensive management of gout.